Effect of DHEA therapy on sexual behavior in female rats. (May 2013) - Pluchino, Nicola; Giannini, Andrea; Cela, Vito; Santoro, Anna N.; Carnevale, Gianluca; Zavatti, Manuela; Di Viesti, Vittoria; Benelli, Augusta; Genazzani, Andrea R.; Zanoli, Paola
Abstract Delta-5 androgen therapies seem to enhance the sexual response in experimental animal models and in clinical trial. This study analyzed the influence of dehydroepiandrosterone (DHEA) administration on receptive and proceptive components of female rat sexual behavior. Ovariectomized (OVX) adult rats were divided in six groups submitted to the following treatments for 4 weeks: DHEA 0.5 and 5 mg/kg, by oral gavage, alone or in combination with estradiol benzoate 3 µg/rat; EB 3 and 10 µg/rat as control groups. All animals received progesterone (500 µg/rat) 4 h before the behavioral tests. All animals were tested for the following: receptivity and proceptivity weekly for 4 weeks; partner preference and paced mating behavior at the end of the treatments. Oral administration of DHEA at 5 mg/kg in EB primed rats was able to significantly increase proceptive behaviors, already after 1 week of treatment. The increase was more marked after 3 and 4 weeks of treatment. Behavioral changes were associated to modifications of circulating and brain level of allopregnanolone and beta-endorphin, although circulating hormonal levels were within a physiological range. Hormonal treatment using physiological doses of delta-5 androgens (DHEA) positively affects sexual motivation in OVX rats.